Acute Toxicity Test of Ekor Naga (Rhaphidophora pinnata (L.f) Schott) Leaf Extract in Mice and Kidney Histological Examination - Fathnur Sani K.; Dian Magfirah; Yuliawati Yuliawati; Elisma Elisma; Uce Lestari (Indonesian Society for Cancer Chemoprevention, 2022)
Ekor Naga (Rhaphidophora pinnata (L.f) Schott) is a traditional plant used by the community. Previous studies have shown that this plant has pharmacological effects, including as anthelmintics, antioxidant, and anti-inflammatory agent as well as promotes wound healing. Thus, it is necessary to do a toxicity test. The study aimed to determine the effect of the extract on histopathology of the kidney through a toxicity test. The research used an experimental design. The test animals were divided into 5 groups, each of which consisted of 5 test animals: negative control (0.5% Na. CMC), Treatment 1 (Extract of ekor naga leaves at a dose of 200 mg/Kg BW), Treatment 2 (Extract of ekor naga leaves at a dose of 600 mg/Kg BW), Treatment 3 (Extract of ekor naga leaves at a dose of 1800 mg/Kg BW), and Treatment 4 (Extract of Ekor Naga Leaves at a dose of 5400 mg/Kg BW). The parameters observed were the Letal Dose (LD50) and the histophatology of the kidney. Data were analyzed using One Way ANOVA test, followed with Duncan’s test. The results showed no significant difference in the weight of the kidney (p>0.05), and the histophatology of the kidney after 14 days of acute administration of ekor naga leaf extract in all the treatment was normal. The administration of ekor naga leaf extract at therapeutic doses and larger doses of single administration did not have a bad effect on the histology of the kidney.Keywords: Ekor Naga Leaves, Kidney, Histopathology, Acute Toxicity.